Spanish Language Pelvic Floor Disorders Patient Information Handouts: How Readable Are They?. Issue 1 (January 2019) - Robb, James; Mackay, Alex; Rondeau, Nancy; Palomino, Javier; Mulla, Zuber D.; Montoya, T. Ignacio; Mallett, Veronica T.
Abstract : Objective: This study aimed to determine the readability of commonly available patient information materials for pelvic floor disorders written in Spanish and compare their readability based on type of content and source. Methods: Spanish patient information handouts, including pamphlets from the National Institutes of Health, International Urogynecology Association, American Congress of Obstetricians and Gynecologists, online printable handouts, and industry-sponsored brochures were assessed for readability. Online materials for patients were obtained from Google searches using key words ( pelvic floor disorders, urogynecology, patient information handouts, Spanish ). Reading difficulty was assessed using INFLESZ v1.0, (Barrio-Cantalejo IM, Spain) a free software developed to calculate the readability of Spanish written texts. Three index scales were used: Flesch-Szigriszt Index, Word correlation Index, and the Fernandez-Huerta Index. Results: Forty patient information handouts were analyzed. All pamphlets analyzed had readability scores within the "average" to "very difficult" reading difficulty levels as per the index scales used. None of the analyzed pamphlets met the sixth grade reading level criteria suggested by the National Institutes of Health and American Medical Association, including government-developed materials. There were no differences in readability scores between type of leaflet content or source. Conclusions: Current available free, industry-, organization-, and government-provided reading materials in Spanish do not serve the Spanish-speaking only or low English-speaking literacy population. Future work should aim to simplify the language in such documents to the suggested sixth grade reading level. Abstract : PFD-related patient information leaflets in Spanish have average to difficult levels of readability.